(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The aim of the study was to study the phytogenic field of uneven-agedd black haloxylon plants by determining their influence on the dynamics of wormwood phytometer species aged spectrum.The black haloxylon phytogenic field was studied by the phytometer method in the Karnabchul desert. The black haloxylon uneven-agedd plants phytogenic fields influence on branching wormwood aged spectrum dynamics depends on the intensity degree of this field. The greatest negative influence of the dificatory species is observed within the middle-agedd generative black haloxylon minimum phytogenic field, as a result of which wormwood aged spectrum gradually acquires a regressive character.